Thyroid Autoimmunity and Lichen - Guarneri, Fabrizio; Giuffrida, Roberta; Di Bari, Flavia; Cannavò, Serafinella Patrizia; Benvenga, Salvatore (Frontiers in Endocrinology, 2017)
Lichen planus and lichen sclerosus are cutaneous-mucous diseases with uncertain epidemiology. Current data, which are likely to be underestimated, suggest a prevalence in the general population of 0.1-4% for cutaneous lichen planus, 1.27-2.0% for oral lichen planus, and 0.1-3.3% for lichen sclerosus. While etiology of lichen is still unknown, clinical and histological evidence show an (auto)immune pathogenesis. Association of lichen with autoimmune thyroid disease has been investigated in few studies. This association appears better defined in the case of lichen sclerosus, while is more controversial for lichen planus. In both situations, the frequency of the association is higher in females. We review the available literature on the correlation between the different types of lichen and autoimmune thyroid disease, and the literature on the genetic risk factors which are shared by both conditions. Such data suggest that a common pathogenic mechanism could be the cause for co-occurrence of lichen and autoimmune thyroid disease, at least in some patients. Additionally, analyzing literature data and in continuity with our previous work on other autoimmune diseases, we suggest that molecular mimicry could trigger both diseases, and thus explain their co-occurrence.